Novel anion-conducting interpenetrating polymer network of quaternized polysulfone and poly(vinyl alcohol) for alkaline fuel cells. (13th April 2016) - Gong, Yujiao; Liao, Xiaofeng; Xu, Jing; Chen, Dongzhi; Zhang, Hongwei
Abstract: Chloromethylated polysulfone is firstly converted to cationic groups under the condition of N, N, N′, N′-tetramethylethylenediamine in dimethyl sulfoxide, then blended with poly(vinyl alcohol) (PVA) solution, followed by casting, crosslinking and treatment in trimethylamine solution for constructing anion-conducting interpenetrating polymer networks (IPNs). Fourier transform infrared spectra, thermogravimetric analysis and scanning electron microscopy are employed to characterize the structure and morphology of IPNs. The properties of IPNs including water uptake, mechanical property, thermal stability and ionic conductivity are studied. Compared with the quaternized polysulfone membrane, the IPN derived from 60% CMPSF and 40% PVA shows better balanced properties. It exhibits an ionic conductivity of 1.82 × 10 −2  S cm −1 at 60 °C and nearly 80% ionic conductivity of the original value after being treated in 2 M NaOH solution for 120 h at 60 °C. Highlights: Strategy for IPN consisted of QPSF and PVA is presented. IPNs exhibit better balanced properties than the plain QPSF membrane. The optimum IPN keeps 78% of original ionic conductivity after stability test.